The Effect of Elevation Differences on the Estimation of Plant Evapotranspiration in the Kuranji Watershed - Anastasia Catur Lestari; Daoed, Darwizal; Nurhamidah; Junaidi (CIVED, 2025)
This study compares evapotranspiration (ETo) values obtained from direct field observations with estimates from empirical models at different elevation. The empirical models used are Modified Penman, Penman-Monteith, Blaney-Criddle, Hargreaves, and Radiation. This research was conducted in the Batang Kuranji Watershed, specifically in Pauh Subdistrict (174 m above sea level) and Nanggalo Subdistrict (18 m above sea level), from August 6th to August 31st, 2023. Daily temperature, humidity, wind speed, and solar radiation data, collected using Thermo-Pro devices and from relevant agencies, were used as input for the empirical models. Three field experiments were carried out in the form of: evaporation plots, evapotranspiration plots without infiltration influence, and evapotranspiration plots with infiltration influence. Furthermore, the observed ETo values in the field were 90.67 mm/month in Nanggalo and 90.00 mm/month in Pauh. The empirical models produced estimates comparable to field observations. Analysis of the coefficient of determination (R²) revealed that the Modified Penman empirical model was the most suitable with field experiments and showed a very strong relationship (R² = 0.96). The results of this study can be used as a basis for managing rice irrigation water and developing better ETo prediction models, especially in the Batang Kuranji Watershed. The authors identify areas needing further research to enable the model's use for calculating evaporation across an entire growing season.